2000
DOI: 10.1038/sj.onc.1203845
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion induced expression of the serine/threonine kinase Fnk in human macrophages

Abstract: Members of the polo subfamily of protein kinases play crucial roles in cell proliferation. To study the function of this family in more detail, we isolated the cDNA of human Fnk (FGF-inducible kinase) which codes for a serine/threonine kinase of 646 aa. Despite the homology to the proliferation-associated polo-like kinase (Plk), tissue distribution of Fnk transcripts and expression kinetics di ered clearly. In contrast to Plk no correlation between cell proliferation and Fnk gene expression was found. Instead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 41 publications
0
57
3
Order By: Relevance
“…It has been reported that PLK3 is overexpressed in adherent vs nonadherent macrophages, and that it interacts with calcium-and integrin-binding protein (CIB), a small protein involved in integrin signalling pathways (Holtrich et al, 2000). As PLK3 is also expressed in irreversible postmitotic cells like neuronal ganglion cells (data not shown), it is intriguing to speculate on the basis of data obtained in neuronal cells (Kauselmann et al, 1999) and in macrophages (Holtrich et al, 2000) that the proposed interaction of PLK3 with CIB might play a role in determining the adhesiveness of tumour cells, albeit functional evidence for such a role of PLK3 in tumours is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PLK3 is overexpressed in adherent vs nonadherent macrophages, and that it interacts with calcium-and integrin-binding protein (CIB), a small protein involved in integrin signalling pathways (Holtrich et al, 2000). As PLK3 is also expressed in irreversible postmitotic cells like neuronal ganglion cells (data not shown), it is intriguing to speculate on the basis of data obtained in neuronal cells (Kauselmann et al, 1999) and in macrophages (Holtrich et al, 2000) that the proposed interaction of PLK3 with CIB might play a role in determining the adhesiveness of tumour cells, albeit functional evidence for such a role of PLK3 in tumours is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Holtrich et al (2000) found that Plk3 transcript levels were higher in adherent primary human monocytes compared to nonadherent cells and these authors suggested that Plk3 could participate in adhesion-related signal transduction pathways. Waelput et al (2000) reported that leptin treatment of a PC12 cell line stably expressing the mouse leptin receptor induced Plk3 mRNA expression.…”
Section: Cells In Culturementioning
confidence: 98%
“…Three groups reported that Plk3 mRNA expression was frequently reduced in lung tumor specimens in comparison to adjacent uninvolved tissue harvested from the same patients (Li et al, 1996;Holtrich et al, 2000;Ando et al, 2004). Also, Plk3 mRNA downregulation has been detected in uterus (Ando et al, 2004), bladder (Ando et al, 2004), and head and neck squamous cell carcinoma (Dai et al, 2000) specimens.…”
Section: Normal Adult Tissues and Tumor Specimensmentioning
confidence: 99%
“…In addition, Plk3 binds to the Ca 2 þ /integrin-binding protein Cib in two-hybrid analyses and in co-immunoprecipitation assays (Kauselmann et al, 1999), and both proteins colocalize in mammalian cells. The homology of Cib with calmodulin and with calcineurin B suggests that Cib might be a Plk regulatory subunit (Holtrich et al, 2000). Lastly, plk3 is an early inducible gene since plk3 mRNA expression in cultured cell lines is rapidly activated by mitogens (Li et al, 1996).…”
Section: The Plk3mentioning
confidence: 99%
“…In addition to its nuclear functions, Plk3 clearly has cytoplasmic roles given its involvement in Golgi breakdown . Furthermore, Holtrich et al (2000) have shown that deregulated Plk3 expression disrupts the cellular Factin network and induces a spherical morphology. In addition, Plk3 binds to the Ca 2 þ /integrin-binding protein Cib in two-hybrid analyses and in co-immunoprecipitation assays (Kauselmann et al, 1999), and both proteins colocalize in mammalian cells.…”
Section: The Plk3mentioning
confidence: 99%